The effect of flow inhomogeneities on airdynamic characteristics of a plane - Воропаев, Г. А.; Розумнюк, Н. В.; Датта, Панчанан (Proceedings of National Aviation University (archive), 2003)
Presented are results of numerical modeling the interaction of a single finite - area vortex or a pair of vortices with a thin plate, on the basis of solution of the nonstationary Navier - Stokes equations.The dependence of friction drag of the plate on initial parameters of vortices has been analyzed